The influence of age on induced sputum differential cell counts in normal subjects. - Thomas, R; Green, R; Brightling, C; Birring, S; Parker, D; Wardlaw, A; Pavord, I (2004)
STUDY OBJECTIVES: Sputum induction is increasingly used as a research technique and as a clinical tool. In order to evaluate abnormal results, normal ranges need to be fully developed. Although a number of studies have described normal ranges, none have investigated the effect of the age of the subject on these results. This study was undertaken to assess whether there are age-related differences in sputum cell differential cell counts in a population of normal, healthy volunteers. STUDY DESIGN AND PARTICIPANTS: Induced sputum samples were obtained from 66 healthy, nonsmoking subjects (24 men) with a mean age of 44 years (age range, 18 to 74 years). Differential cell counts were related to age. RESULTS: Sputum neutrophil counts were found to correlate significantly with the age of the volunteers (r = 0.58; p < 0.001). Macrophage counts showed a proportionate, inverse correlation with increasing age (p < 0.01), but no correlation was seen for any other cell type. On subanalysis according to age range, the mean neutrophil differential increased from 26.9% (SD, 19.8%) [17 patients] in the group of patients who were 0 to 29 years of age to 68.5% (SD, 20.6%) [11 patients] in the group of patients who were > 60 years of age. CONCLUSION: In our healthy volunteer population, the induced sputum differential neutrophil count increased significantly with age. These findings highlight the need for age matching in controlled studies.